Synthesis of TiO2-based photoelectrode and natural dye for dye sensitized solar cell (DSSC). Issue 1 (May 2021) - Mursal,; Malahayati,; Azmi, N; Fatmiyah, S
Abstract: Synthesis and characterization of Mg and La doped TiO2 photoelectrodes and natural dye have been studied. This study aimed to analyze the effect of Mg and La concentration on the characteristics of Mg and La doped TiO2 and to investigate the characteristic of natural dye extracted from green spinach, red spinach, and mangosteen rind. Mg and La doped TiO2 were synthesize by sol-gel method using titanium (IV) isopropoxide, magnesium acetate and lanthanum (III) acetate as precursors. The concentration of Mg and La were varied from 0 – 4% mol. Mg and La doped TiO2 films were deposited on glass substrate by using doctor blade technique and annealed at 500°C for 1 h. The films were then characterized using X-Ray Diffractometer and UV-Vis spectrometer measurement to investigate its characteristics. The results showed that dopant concentration strongly affected the structural and optical properties of Mg and La doped TiO2 . The UV-Vis measurement of the natural dye extracted from green spinach, red spinach, and mangosteen rind showed a different absorption spectrum. However, FTIR measurement of these dyes showed relatively the similar spectrum. This shows that each dye has different optical properties, even though it has relatively the same functional group.